MATHEMATICAL UNDERSTANDING CAPABILITY OF SENIOR HIGH SCHOOL NUMBER 1 STUDENTS THROUGH LEARNING ASSISTED GRAPHER APPLICATION ON ANDROID - Yanna Sanova; Ely Susanti; Ayu Mentari (Sriwijaya University Learning and Education International Conference, 2018)
This research is a descriptive study that aims to describe the ability to understand mathematical concepts in grade 12 7 in SMA 1 Palembang through learning assisted Grapher application on android. The subjects of this study consisted of 30 students. The instrument used was observation and test. Observations were used to collect data about learning and tests were used to see the ability to understand students' mathematical concepts. The results of the study concluded that the ability of students' understanding of rational function material, limitless to algebraic functions and infinite limits on categorized trigonometric functions was quite good. In the material of rational function, students were misconstrued due to being trapped in images that appear to be congruent. Even though the pictures were not congruent. Still related to the material of rational function, the presentation of a picture that was not right in terms of scale and form of sketches caused students to misinterpret the problem and make conclusions. Specifically for infinite limit material for both algebraic and trigonometric functions, the low scores of students on the concept comprehension tests were caused by students being less careful in calculating.